Expression of Latent HIV Induced by the Potent HDAC Inhibitor Suberoylanilide Hydroxamic Acid - Archin, Nancie M. (Mary Ann Liebert, Inc., 2009)
Histone deacetylases (HDACs) act on histones within the nucleosome-bound promoter of human immunodeficiency virus type 1 (HIV-1) to maintain proviral latency. HDAC inhibition leads to promoter expression and the escape of HIV from latency. We evaluated the ability of the potent inhibitor recently licensed for use in oncology, suberoylanilide hydroxamic acid (SAHA; Vorinostat), selective for Class I HDACs, to induce HIV promoter expression in cell lines and virus production from the resting CD4(+) T cells of antiretroviral-treated, aviremic HIV-infected patients. In J89, a Jurkat T cell line infected with a single HIV genome encoding the enhanced green fluorescence protein (EGFP) within the HIV genome, SAHA induced changes at nucleosome 1 of the HIV promoter in chromatin immunoprecipitation (ChIP) assays in concert with EGFP expression. In the resting CD4(+) T cells of antiretroviral-treated, aviremic HIV-infected patients clinically achievable exposures to SAHA induced virus outgrowth ex vivo. These results suggest that potent, selective HDAC inhibitors may allow improved targeting of persistent proviral HIV infection, and define parameters for in vivo studies using SAHA.